Diagnosis and monitoring of HIV infection - A.J. Glass (South African Family Practice)
The latest statistics indicate that the number of people infected with human immunodeficiency virus type 1 (HIV-1) worldwide in 40.3 million, 25.8 million of whom live in sub-Saharan Africa. In 2004, 29.5% of South African women attending antenatal clinics were infected. The virus infects people of all ages and social classes. A diagnosis of HIV has serious physical, emotional and social implications for the patient. HIV-infected patients are susceptible to numerous opportunistic and other infections, as well as to non-infectious diseases such as tumours. They eventually require lifelong treatment with potentially toxic medication. It in therefore essential that a timeous and correct diagnosis be made. An understanding of the tests available for the diagnosis and monitoring of HIV in essential for all clinicians working in South Africa. Tests available for the diagnosis of HIV in patients older than 18 months include HIV-specific antibody assays, fourth-generation combination antibody-antigen assays and Western Blot. The diagnosis of HIV infection in infants younger than 18 months requires detection of the virus itself by means of p24 antigen detection or HIV DNA PCR. The CD4+ T lymphocyte count and HIV viral load are used for monitoring disease progression and response to therapy.